2006
DOI: 10.1536/ihj.47.549
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Age-Related Changes in 24-Hour Total Heart Beats and Premature Beats and Their Relationship in Healthy Elderly Subjects

Abstract: SUMMARYThe aim of this study was to conduct a longitudinal follow-up on age-related changes in 24-hour total heart beats (THBs) and total premature beats and their correlations in healthy elderly subjects. In 15 healthy elderly subjects (mean age, 70.0 ± 4.1, age range at 1st recording, 64 to 80 years, 10 females, 5 males), we conducted Holter monitoring twice at an interval of 15 years and analysed age-related changes in THBs, atrial premature beats (APBs), and ventricular premature beats (VPBs), as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…The Framingham Heart Study reported a 1.9-fold higher risk of AF in hypertensive than in normotensive individuals (15). Frequent PACs have also been reported in hypertensive patients and in elder subjects (28). The inter-individual variability in the number of AT episodes in the 24-h recordings further supported the close resemblance between this model and the human presentation of AT.…”
Section: Discussionsupporting
confidence: 57%
“…The Framingham Heart Study reported a 1.9-fold higher risk of AF in hypertensive than in normotensive individuals (15). Frequent PACs have also been reported in hypertensive patients and in elder subjects (28). The inter-individual variability in the number of AT episodes in the 24-h recordings further supported the close resemblance between this model and the human presentation of AT.…”
Section: Discussionsupporting
confidence: 57%
“…In healthy elderly subjects, total heart beats as well as atrial and ventricular premature beats increase with age, and this increase in premature beats is in proportion to total heart beats (Tasaki et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Although, previous studies demonstrated that incidence of ventricular ectopy (Premature Ventricular Contraction, PVC) increases with age [7], but to the best of our knowledge its association with frailty, a geriatric syndrome that is associated with adverse health outcomes, has not been studied. An increased prevalence of ventricular ectopy is associated with increased incidence of congestive heart failure (CHF) and increased mortality [8].…”
Section: Introductionmentioning
confidence: 93%